Coordination Function of the Camat in Disaster Management in Central Sinjai District, Sinjai Regency - Supratman Tahir; Mulawangsa Mappakalu; Sofyang Sofyang; Susisusanti Susisusanti (Universitas Negeri Makassar, 2022)
Natural phenomena that hit the District of Central Sinjai almost every year, especially landslides, it is necessary to strive to reduce the risk of these disasters so that it is hoped that the Government will optimize coordination in tackling these disasters. This study aims to determine the coordination function of the Government in Disaster Management in Central Sinjai District, Sinjai Regency. The type of research is qualitative, data collection techniques are observation, interviews and documentation. The informants consisted of the Head of the Central Sinjai Sub-district, the Head of the Public Order and Peace Section, the Head of the Emergency and Logistics Division at the Regional Disaster Management Agency (BPBD) of Sinjai Regency, and the Village Head. The data analysis technique was carried out by means of data reduction, data display and conclusions. The results showed that the sub-district coordination function in disaster management in Central Sinjai District, Sinjai Regency was quite maximal, both vertical coordination and horizontal coordination.